DAMPAK AKTIVITAS FISIK PADA PENINGKATAN KESEHATAN TULANG PADA REMAJA : STUDI LITERATUR - Muhammad Akbar Syafruddin; Nur Indah Atifah Anwar (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2026)
This study uses a literature review method to analyze and synthesize information from various studies that have been conducted related to the impact of physical activity on adolescent bone health. The data used in this study came from scientific journals, research articles, books, and reports published in the last 10 years. Data was taken from trusted academic platforms such as PubMed, ScienceDirect, Google Scholar, and national journal portals such as Garuda. Data was collected using certain keywords such as "benefits of physical activity for adolescent bones", "bones and sports", and "adolescent bone health". After the search was conducted, relevant articles were identified and selected based on the inclusion and exclusion criteria that had been set. Data analysis was carried out descriptively to conclude relevant research findings. In conclusion, this study highlights the importance of a holistic approach in supporting bone health. The combination of weight-bearing exercise, optimal nutrition, and injury risk management strategies can provide maximum benefits. By considering individual differences, such as gender, health conditions, and physical activity preferences, appropriate intervention strategies can be applied to support bone health throughout the life cycle.